Persian pottery in the first global age - Golombek, Lisa.
1 online resource.
Keywords: Persian Pottery in the First Global Age: the Sixteenth and Seventeeth Centuries studies the ceramic industry of Iran in the Safavid period (1501–1732) and the impact which the influx of Chinese blue-and-white porcelain, heightened by the activities of the English and Dutch East Indies Companies after c. 1700, had on local production. The multidisciplinary approach of the authors (Lisa Golombek, Robert B. Mason, Patricia Proctor, Eileen Reilly) leads to a reconstruction of the narrative about Safavid pottery and revises commonly accepted notions. The book includes easily accessible reference charts to assist in dating and provenancing Safavid pottery on the basis of diagnostic motifs, potters’ marks, petrofabrics, shapes, and Chinese models.